2007
DOI: 10.1523/jneurosci.0700-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1/DCC Signaling in Commissural Axon Guidance Requires Cell-Autonomous Expression of Heparan Sulfate

Abstract: There is increasing evidence that heparan sulfate (HS) plays an essential role in various axon guidance processes. These observations, however, have not addressed whether HS is required cell autonomously as an axonal coreceptor or as an environmental factor that modulates the localization of guidance molecules in the terrain in which growing axons navigate. Here we demonstrate that netrin-1-mediated commissural axon guidance requires cell-autonomous expression of HS in commissural neurons in vivo. We used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 49 publications
2
65
0
1
Order By: Relevance
“…In the cases of FGF2 and netrin-1, HS acts as an essential coreceptor, for ligand interaction with the cognate receptors that activate downstream signaling (38,39). Our analysis of mutant limb buds and micromass cultures revealed that the intensity of BMP signaling is somewhat impaired, but not entirely abolished, in the absence of HS.…”
Section: Discussionmentioning
confidence: 81%
“…In the cases of FGF2 and netrin-1, HS acts as an essential coreceptor, for ligand interaction with the cognate receptors that activate downstream signaling (38,39). Our analysis of mutant limb buds and micromass cultures revealed that the intensity of BMP signaling is somewhat impaired, but not entirely abolished, in the absence of HS.…”
Section: Discussionmentioning
confidence: 81%
“…This has been suggested to be an effect of a transient reduction in HS-dependent fibroblast growth factor signaling during embryogenesis. Moreover, heparan sulfate and chondroitin sulfate proteoglycans (HSPGs and CSPGs, respectively) serve different functions during brain development, with CSPGs inhibiting and HSPGs promoting axon extension (50). GPC1 is exclusively substituted with HS, whereas GPC5, for example, can exist as an HS CS/DS (where DS is dermatan sulfate) hybrid.…”
Section: Discussionmentioning
confidence: 99%
“…Signals generated by the engagement of ephrin ligands to Eph receptors generally result in repulsive responses, such as retraction of the cell periphery and cell rounding, and growth cone collapse in neurons. These repulsive responses are thought to be the basis for the function of the ephrin-Eph system in axon guidance.The function of many important morphogens and guidance molecules has been shown to involve accessory molecules as coreceptors or as a mechanism to control the topological distribution of the guidance molecules (7,8,(12)(13)(14). Curiously, there is little information on whether ephrin-Eph signaling is influenced by heparan sulfate or other accessory regulatory molecules.…”
mentioning
confidence: 99%
“…The function of many important morphogens and guidance molecules has been shown to involve accessory molecules as coreceptors or as a mechanism to control the topological distribution of the guidance molecules (7,8,(12)(13)(14). Curiously, there is little information on whether ephrin-Eph signaling is influenced by heparan sulfate or other accessory regulatory molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation